CHRONIC CYCLIC BLADDER OVER-DISTENSION UPREGULATES HYPOXIA-DEPENDENT PATHWAYS - Stephany, Heidi A. (2013)
PURPOSE: Bladder over-distension secondary to anatomic or functional obstruction can eventually lead to pathologic changes, including decreased elasticity and contractile dysfunction. We hypothesize that chronic bladder distension in a murine model will activate hypoxia-dependent signaling pathways despite intermittent relief of the distention. METHODS: Female C57Bl/6 mice were oophorectomized at 5–6 weeks and subjected to urethral catheterization and 90 minutes of bladder distension. Acute and chronic time points were evaluated. Bladder tissue was harvested for H&E staining and for immunohistochemical (IHC) staining with the hypoxia markers, glucose transporter-1 and Hypoxyprobe™-1. Bladder tissue was also harvested for RT-PCR and measurement of oxidative stress. Hypoxia PCR Arrays were performed to determine changes in gene expression. Oxidative stress was measured using F2-Isoprostanes (F2-IsoP). Functional changes in the bladder were evaluated using voided urine blots. RESULTS: After acute distension and 5 consecutive distensions, bladders exhibited marked inflammatory changes on H&E staining and evidence of tissue hypoxia by IHC. qRT-PCR demonstrated up-regulation of hypoxia and oxidative stress related genes including Hif1a, Arnt2, Ctgf, Gpx1, and Hmox1. Measurements of oxidative stress with F2-IsoP did not change. Voided urine blots before and after bladder distension demonstrated marked changes showing an overactive voiding pattern. CONCLUSION: Chronic bladder distension is possible in the female mouse and does generate a hypoxic injury characterized functionally by increased voiding patterns. This bladder injury model might more closely replicate bladder dysfunction in patients with poor bladder emptying due to neurologic disease including patients who are noncompliant with intermittent catheterization.